2021
DOI: 10.3390/ijerph18073683
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Gender Differences in Factors Affecting Depression among Multicultural Adolescents in South Korea: A Cross-Sectional Study

Abstract: Suicide is the topmost cause of death among adolescents in South Korea and is deeply related to depression. This study aimed to identify gender differences in the factors affecting depression among multicultural adolescents. This study is a secondary analysis using data from a national survey, the Multicultural Adolescents Panel Study (MAPS) conducted in 2017. The participants were 1160 multicultural adolescents ranging from 15 to 18 years, living in Korea, and whose fathers were Koreans and mothers were forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…The discrepancy could be due to various biological and psychosocial disparities in females. While female counterparts experience variable adverse stressors, their temperament and response to these stressors play an integral part in the development of depression [19].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy could be due to various biological and psychosocial disparities in females. While female counterparts experience variable adverse stressors, their temperament and response to these stressors play an integral part in the development of depression [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these mixed findings on the association between socioeconomic status and depression, prevalence of depression has been found to be fairly common among South Korean adolescents, with prevalence rates ranging from across a number of studies [ 1 , 3 , 14 ]. Of note, the recent COVID-19 pandemic has also contributed to increased depression among adults in South Korea and adolescents in other countries, including Australia, China, and the United States [ 6 , 15 , 16 , 17 ]. Such increases in depression have been particularly evident among low-income adolescents or among adolescents whose parents have experienced a job loss [ 18 , 19 , 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have found that experiencing parental neglect during adolescence is positively associated with adolescents’ depression [ 4 , 5 , 6 , 7 ]. First, in a study of multicultural adolescents living in South Korea with a Korean father and a non-Korean mother, adolescents who reported that their parents engaged in a neglectful parenting style had higher depression than those who did not [ 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations